2016
DOI: 10.4103/0019-5413.181797
|View full text |Cite
|
Sign up to set email alerts
|

Trends in scientific publications of Indian spine surgeons over 14 years (2000–2013)

Abstract: Background:The number and quality of scientific publications reflects the standards of scientific research in a country. However, the contribution of Indian spine surgeons toward global publications is unknown. The goal is to study the publications of Indian spine surgeons between 2000 and 2013.Materials and Methods:A literature search of the publications by Indian spine surgeons was performed using MEDLINE. The search terms used were India and several spine-related terminologies. The main information of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Bibliometric analysis methods have shown efficacy in assessing research development in specific fields (9). Multiple studies have dealt with the bibliometric analysis of research output from confined geographical areas (4)(5)(6)(7)(8)(9). A previous study by the authors of the current study (SB, YM) has found that Saudi research output in spine surgery was low in quality and numbers (11).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Bibliometric analysis methods have shown efficacy in assessing research development in specific fields (9). Multiple studies have dealt with the bibliometric analysis of research output from confined geographical areas (4)(5)(6)(7)(8)(9). A previous study by the authors of the current study (SB, YM) has found that Saudi research output in spine surgery was low in quality and numbers (11).…”
Section: Discussionmentioning
confidence: 88%
“…The progress of countries, both economically and scientifically, depends on their involvement in research and innovation (6). Bibliometric analysis methods have shown efficacy in assessing research development in specific fields (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 15 16 Besides these, various authors have attempted to find the most-cited papers in the different subspecialties of orthopaedics; 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 and also, influential papers from a particular region. 34 35 36 37 38 39 40 41 42 …”
Section: Introductionmentioning
confidence: 99%
“…The number of scientific papers contributed by each country toward the global research output, along with the number of citations received by them, has become one of the critical indicators for assessing the strength of research in a nation. 37 The disease patterns and patient demands also vary for each country, and a study of influential articles from a particular country throws light on the locally prevalent health problems and attempts made at solving them, besides global scientific contributions.…”
Section: Introductionmentioning
confidence: 99%